Perlindungan Hukum terhadap Pemenuhan Hak-Hak Pekerja dalam Hubungan Industrial (Studi Kasus Putusan Pengadilan Jakarta Pusat Nomor 17/Pdt.Sus-Phi/2025/Pn.Jkt.Pst - Topan Ridwan; Suriyanto Suriyanto (FOCUS, 2026)
Industrial relations are fundamentally intended to create a balance of rights and obligations between employers and workers; however, in practice, disputes frequently arise, particularly concerning the fulfillment of workers’ normative rights. This study aims to analyze the types of workers’ rights disputed and the legal considerations applied by the judges in the Decision of the Industrial Relations Court at the Central Jakarta District Court Number 17/Pdt.Sus-PHI/2025/PN.Jkt.Pst. This research employs a normative (doctrinal) legal method conducted through library research by examining statutory regulations and court decisions. The findings indicate that the dispute arose due to the employer’s failure to fulfill legal obligations, including unilateral wage deductions, failure to register workers in social security programs, and non-payment of workers’ entitlements after the termination of employment. The Panel of Judges rejected the Defendant’s exception and partially granted the Plaintiff’s claims by ordering the payment of outstanding workers’ rights amounting to IDR 94,362,969.00 to be paid in installments over four months, while other claims were dismissed. This decision underscores the importance of protecting workers’ normative rights and reaffirming employers’ legal responsibilities within industrial relations.